2019
DOI: 10.1016/j.bbrc.2018.12.059
|View full text |Cite
|
Sign up to set email alerts
|

Identification of myosin II as a cripto binding protein and regulator of cripto function in stem cells and tissue regeneration

Abstract: Cripto regulates stem cell function in normal and disease contexts via TGFbeta/activin/nodal, PI3K/Akt, MAPK and Wnt signaling. Still, the molecular mechanisms that govern these pleiotropic functions of Cripto remain poorly understood. We performed an unbiased screen for novel Cripto binding proteins using proteomics-based methods, and identified novel proteins including members of myosin II complexes, the actin cytoskeleton, the cellular stress response, and extracellular exosomes. We report that myosin II, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…In a notable example of this, Wicha and colleagues showed that certain stem cell populations (i.e., ALDH+ cells) reside in stressed tumor microdomains and increase following antiangiogenic, hypoxia-inducing therapy (Avastin) [52]. It remains to be determined if other critical cell processes like metabolism or trafficking, which may also be under CRIPTO control [53,54], are critical contributors to overall cellular plasticity and adaptability.…”
Section: Discussionmentioning
confidence: 99%
“…In a notable example of this, Wicha and colleagues showed that certain stem cell populations (i.e., ALDH+ cells) reside in stressed tumor microdomains and increase following antiangiogenic, hypoxia-inducing therapy (Avastin) [52]. It remains to be determined if other critical cell processes like metabolism or trafficking, which may also be under CRIPTO control [53,54], are critical contributors to overall cellular plasticity and adaptability.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a recent proteomic analysis of the Cripto-1 interactome identified 51 Cripto-1 binding proteins from human epithelial cells including regulators of extracellular exosomes, myosin II complexes, and the cytoskeleton. The myosin II activity was shown to regulate subcellular localization of Cripto-1 in epithelial and mesenchymal stem cell populations and to function cooperatively with zebrafish Cripto-1 to promote caudal fin regeneration [50]. Although we were unable to localize cripto-1 expression in the fin, these new data suggest that Cripto-1 may be expressed in both epithelial and mesenchymal cells following BDP exposure.…”
Section: Discussionmentioning
confidence: 75%
“…An unbiased screen for novel Cripto binding proteins using a non-transformed human mammary epithelial cell line (MCF10A) expressing a Flag-Cripto protein identified Myosin 9 (MYH9), a member of the Myosin II complex, as a Cripto interactor. The treatment of MCF10A Flag-Cripto cells with Myosin II inhibitor impaired Cripto localization to the cell membrane and its release in the culture media [82].…”
Section: Cripto Signaling In Biochemistry and Molecular Biologymentioning
confidence: 94%